Breaking International Barriers: #ColorectalSurgery Is #GlobalSurgery - Mayol, Julio; Otero, Jaime (Clinics in Colon and Rectal Surgery, 2017)
Colorectal surgeons have lagged behind other professionals in the use of social media. Currently, Twitter is the most widely utilized social platform for professional purposes among them. Connection and contagion are the two key actions that, together with immediate feedback and quantifiable impact, favor the use of Twitter over other social networks. In early 2016, a group of colorectal surgeons launched the #colorectalsurgery hashtag and, in less than 1 year, the ecosystem has incorporated over 2,600 users that generated over 24,000 tweets and 100 million impressions. “Live-Tweeting” surgical conferences by attendees including institutional or society accounts have greatly contributed to the success of the initiative. However, there are some barriers to a more wide adoption of social media, such as misrepresentation of non–peer-reviewed data, challenges to intellectual property protection, or even damage to the professional image. Active engagement with the #colorectalsurgery community may result in benefits for the global surgery community through information sharing, social interactions, personal branding, and research.
Keywords: Twitter; #colorectalsurgery; conference; hashtag; social media; surgery